Multifunctional Photo-Cross-Linking Probes: From Target Protein Searching to Imaging Applications - Kozoriz Kostiantyn; Shkel, Olha Viktorivna; Kyung tae Hong; Kim Dong Hoon; Kim Yun Kyung; Lee Jun-Seok (American Chemical Society, 2023)
CONSPECTUS: Despite advances in genome sequencing technology, the complete molecular interaction networks reflecting the biological functions of gene products have not been fully elucidated due to the lack of robust molecular interactome profiling techniques. Traditionally, molecular interactions have been investigated in vitro by measuring their affinity. However, such a reductionist approach comes with throughput constraints and does not depict an intact living cell environment. Therefore, molecular interactions in live cells must be captured to minimize false-positive results. The photo-cross-linking technique is a promising tool because the production of a temporally controlled reactive functional group can be induced using light exposure. Photoaffinity labeling is used in biochemistry and medicinal chemistry for bioconjugation, including drug and antibody conjugation, target protein identification of bioactive compounds, and fluorescent labeling of target proteins. This Account summarizes recent advances in multifunctional photo-cross-linkers for drug target identification and bioimaging. In addition to our group's contributions, we reviewed the most notable examples from the last few decades to provide a comprehensive overview of how this field is evolving. Based on cross-linking chemistry, photo-cross-linkers are classified as either (i) reactive intermediate-generating or (ii) electrophile-generating. Reactive intermediates generating photoaffinity tags have been extensively modified to target a molecule of interest using aryl azide, benzophenone, diazirine, diazo, and acyl silanes. These species are highly reactive and can form covalent bonds, irrespective of residue. Their short lifetime is ideal for the instant capture and labeling of biomolecules. Recently, photocaged electrophiles have been investigated to take advantage of their residue selectivity and relatively high yield for adduct formation with tetrazole, nitrobenzyl alcohol, o-nitrophenylethylene, pyrone, and pyrimidone. Multifunctional photo-cross-linkers for two parallel practical applications have been developed using both classes of photoactivatable groups. Unbiased target interactome profiling of small-molecule drugs requires a challenging structure-activity relationship study (SAR) step to retain the nature or biological activity of the lead compound, which led to the design of a multifunctional "minimalist tag" comprising a bio-orthogonal handle, a photoaffinity labeling group, and functional groups to load target molecules. In contrast, fluorogenic photo-cross-linking is advantageous for bioimaging because it does not require an additional bio-orthogonal reaction to introduce a fluorophore to the minimalist tag. Our group has made progress on minimalist tags and fluorogenic photo-cross-linkers through fruitful collaborations with other groups. The current range of photoactivation reactions and applications demonstrate that photoaffinity tags can be improved. We expect exciting days in the rational design of new multifunctional photo-cross-linkers, particularly clinically interesting versions used in photodynamic or photothermal therapy.